New light on Manichaeism : papers from the Sixth International Congress on Manichaeism, organized by the International Association of Manichaean Studies - BeDuhn, Jason. (Nag Hammadi and Manichaean Studies, 2009)
New Light on Manichaeism provides the latest discoveries and insights into the Manichaean religion throughout its more than one thousand year history, ranging from glimpses into the life and thought of Mani himself, to developments in doctrine and practice in the religion's North African, Iranian, Central Asian, and Chinese settings. The volume includes contributions from the leading scholars in the field, offering new reconstructions of Manichaean literary and artistic productions, and innovative analyses of the religious, social, and political dynamics that shaped the rise and fall of this world religion.